Academic development for tomorrow? Claiming a clearer role for university pedagogy through a holistic framework - Lindén, Jyri; Ripatti-Torniainen, Leena; Annala, Johanna (Scandinavian journal of educational research, 2025)
The aim of this theoretically oriented article is to promote the educational role and purpose of academic development in higher education by suggesting a holistic framework and theoretical articulation for university pedagogy. By discussing links between university pedagogy, academic development, and broader views of university education, our framework clarifies the concept of university pedagogy in the Nordic countries. The framework encompasses four themes: (1) the relationship between educational theory and pedagogical practice; (2) the interplay between knowledge and the curriculum; (3) the university as an organization and social institution; and (4) the agency in and of academic communities. We argue that university pedagogy operating within this framework has the potential to strengthen the scholarly foundations of the development of university education. The framework can enhance critical public discourse on the purpose of university education.